1996
DOI: 10.1123/jsm.10.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Retention Factors in Coaching and Athletic Management Positions

Abstract: Within intercollegiate athletic work environments, the retention of coaches and athletic administrators continues to be an issue. Understanding the factors considered important for retaining coaching and athletic management positions has potential significance for reversing the decline of the number of individuals, in particular, women, from these positions, and for increasing the attractiveness of such career pathways. This study developed a scale of retention factors that resulted in three empirically suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 1 publication
4
46
0
Order By: Relevance
“…Many C-SECATs spoke of a ''family-like,'' highly supportive athletic training staff that worked well together, assisted when challenges arose, and respected each other's duties. Our results agree with those of Inglis et al, 25 who found that colleagues' understanding, recognition of contributions, and overall support were key factors in the retention of coaches. With regard to female NCAA D-I ATs, our findings also agree with those of Rice et al, 22 who noted that coworkers' support contributed positively to life balance and that spousal support was key in their strategies to managing family and career demands.…”
Section: The Social Support Paradigm and Retentionsupporting
confidence: 93%
See 2 more Smart Citations
“…Many C-SECATs spoke of a ''family-like,'' highly supportive athletic training staff that worked well together, assisted when challenges arose, and respected each other's duties. Our results agree with those of Inglis et al, 25 who found that colleagues' understanding, recognition of contributions, and overall support were key factors in the retention of coaches. With regard to female NCAA D-I ATs, our findings also agree with those of Rice et al, 22 who noted that coworkers' support contributed positively to life balance and that spousal support was key in their strategies to managing family and career demands.…”
Section: The Social Support Paradigm and Retentionsupporting
confidence: 93%
“…Administrative and supervisory support can play a critical role in retaining qualified, longterm employees and in their overall success. 16,25 Our findings support those of previous researchers who examined the importance of organizational social support in health care organizations. Price 24 and Price and Mueller 26 performed extended research on a causal model of turnover and noted that the amount of administrative and supervisory support within an organization can heavily influence overall job satisfaction, organizational commitment, and intent to stay.…”
Section: The Social Support Paradigm and Retentionsupporting
confidence: 88%
See 1 more Smart Citation
“…These relationships were important for both competence development and relatedness. The desire for mentoring and formal and informal networking among coaches is consistent with research (e.g., Inglis et al, 1996;Kilty, 2006;West et al, 2001). However, the inclusion of the concept of need satisfaction helps to explain why they are important.…”
Section: Discussionsupporting
confidence: 71%
“…Theberge (1993) found that women coaches were marginalized and held a token status in which gender was highlighted through stressing physical differences between men and women and noting of the superiority of men's sporting experiences. Inglis, Danylchuck and Pastore (1996) identified three factors in their development of a work retention scale for coaching. These factors emphasized the social context within which coaches worked including organizational support, recognition of coaches contributions, and fostering collegial respect.…”
mentioning
confidence: 99%